Optimization of Rhombus Opening Area of Shear Walls On Tall Buildings - Syamsir, Agusril; Iskandar, Isdaryanto; Malekzadah, Abdul Rahman; Alhayek, Abdulrahman (International Journal of Integrated Engineering, 2023)
This research was designed to determine the optimum percentage and configuration of rhombus opening on shear wall of tall building. A residential tall building of 12-storeys having base size of 20m Ã— 10m with height of floor of 3m was analysed. In this paper, percentages of 12%, 24%, 36%, 42%, and 54% concentric rhombus opening in a shear wall in tall buildings were modeled. The effect of the opening size on the lateral displacement, base shear, and stress at the opening was determined. It was found that the opening of 12% has less lateral displacement, base shear, and stress at the opening. This indicates that this opening delivers the best performance among the other percentages. Five models with the same percentage of rhombus opening of 12% at different configuration on the shear wall in tall buildings were modeled to determine the optimum configuration of opening on shear walls. It was found that Model-1 is the optimum configuration since this model has the lowest lateral displacement and stress at the opening. It can be concluded that Model-1 with 12% opening area is the optimum size and configuration to resist lateral force on tall buildings.